2011
DOI: 10.1107/s1600536811007598
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-3-(2-Anthracen-2-yl)-1-(2-hydroxyphenyl)prop-2-en-1-one

Abstract: The asymmetric unit of the title compound, C23H16O2, contains two independent mol­ecules in which the dihedral angles between the anthracene ring system and the benzene ring are 73.0 (3) and 73.3 (3)°. In both independent mol­ecules, the hy­droxy group is involved in an intra­molecular O—H⋯O hydrogen bond. The crystal packing is stabilized by π–π inter­actions [centroid–centroid distances = 3.6518 (9), 3.7070 (9) and 3.7632 (9) Å] and weak inter­molecular C—H⋯O hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For the background to chalcones, see: Awad et al (1960); Coudert et al (1988); Insuasty et al (1992Insuasty et al ( , 1997; Kolos et al (1996); Samshuddin et al (2010); Fun et al (2010); ; Shettigar et al (2010); Sharma et al (1997); Ravishankar et al (2003Ravishankar et al ( , 2005; Butcher et al (2006); Narayana et al (2007); Sarojini et al (2007a,b); Jasinski et al (2011). For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the background to chalcones, see: Awad et al (1960); Coudert et al (1988); Insuasty et al (1992Insuasty et al ( , 1997; Kolos et al (1996); Samshuddin et al (2010); Fun et al (2010); ; Shettigar et al (2010); Sharma et al (1997); Ravishankar et al (2003Ravishankar et al ( , 2005; Butcher et al (2006); Narayana et al (2007); Sarojini et al (2007a,b); Jasinski et al (2011). For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Chalcones are also finding application as organic nonlinear optical materials (NLO) for their SHG conversion efficiency (Sarojini et al, 2006;Shettigar et al, 2010). The crystal structures of some of the related chalcones viz: 1-(3,4-dimethoxyphenyl)-3-(3-methylphenyl)prop-2-en-1-one (Sharma et al, 1997), 3-(3,4-dimethoxyphenyl)-1-(4-hydroxy-phenyl)prop-2-en-1-one (Ravishankar et al, 2003), 1-(4chlorophenyl)-3-(4-hydroxyphenyl)prop-2-en-1-one (Ravishankar et al, 2005) (Sarojini et al, 2007a,b) and (2E)-3-(2-anthryl)-1-(2-hydroxyphenyl)prop-2-en-1-one (Jasinski et al, 2011) have been reported. In a continuation of our studies of the structures of chalcones, we report the crystal structure of a new chalcone, (2E)-3-(3-benzyloxyphenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one, C 22 H 18 O 3 , (I).…”
Section: S1 Commentmentioning
confidence: 99%
“…For the previous structure determination, see: Jasinski et al (2011). For a related structure and background references, see: Joothamongkhon et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…From our previous work, which revealed that a chalcone derivative containing the anthracene moiety displayed fluorescence (Joothamongkhon et al, 2010), the title compound (I) was synthesized by changing the substituent group on the phenyl ring for comparison of their properties. It was then discovered that a recent study of the same structure (Jasinski et al, 2011) contained errors in the title, scheme and synthesis. It was found that (I) exhibits fluorescence with the maximum emission at 438 nm when excited at 380 nm in chloroform solution.…”
Section: S1 Commentmentioning
confidence: 99%
“…search of the Cambridge Structural Database (Version 5.40, last update February 2019;Groom et al, 2016) revealed six closely related fused-ring chalcones, namely, trans-3-(9-anthryl)-1-(4-methoxyphenyl)prop-2-en-1-one (refcode EMULIT; Zhang et al, 2016), 3-(anthracen-9-yl)-1-(4-chlorophenyl)prop-2-en-1-one (JAHPUG; Yu et al, 2017), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one (POP-BAY;Suwunwong et al, 2009), (Z)-3-(anthracen-9-yl)-1-(2ethoxyphenyl)prop-2-en-1-one (KABHUS; Joothamongkhon et al, 2010), (E)-3-(anthracen-9-yl)-1-(2-hydroxyphenyl)prop-2-en-1-one (UNUDUD;Jasinski et al, 2011; UNUDUD01;Chantrapromma et al, 2011), (E)-3-(anthracen-9-yl)-1-(2bromophenyl)prop-2-en-1-one (WAFGOB;Fun et al, 2010).…”
mentioning
confidence: 99%